ENGLISH-EFFECT OF CONTENTS PRESENTED ON MEDIA ON THE VOTING BEHAVIOR OF RELIGIOUS PEOPLE IN PAKISTAN - Ali Hassan; Muhammad Shahzad; Ishtiaq Gondal (دی اسکالر)
Today, a great emphasis has been established in the understanding the voting behavior of the people and religion is a strong segment of person's voting behavior. It is the most important aspect for a voter in the way of thinking about specific issues such as ideology, construction of personality, economics and society. Therefore, religion has a significant impact on the behavior of an individual when voting in elections is concerned. In democratic countries like Pakistan media has gained more importance in this regard. The present study focuses on effects of the contents presented in media on the voting behavior of religious people voting for religious parties in general elections 2013,local bodies’ elections 2015 and general elections 2018.